Potential Predictors and Survival Analysis of the Relapse of HIV-Associated Cryptococcal Meningitis: A Retrospective Study - Li, Yao; Lu, Yanqiu; Nie, Jingmin; Liu, Min; Yuan, Jing; Li, Yan; Li, Huan; Chen, Yaokai (Frontiers in Medicine, 2021)
Objective We intend to investigate the relapse of HIV-associated cryptococcal meningitis (CM), assess potential predictors, and conduct survival analysis, with a view to establishing a valid reference for the management of the relapse of CM. Method This is a retrospective study in Chinese patients with HIV-associated CM and those who experience relapse of CM. Baseline demographic, laboratory, and clinical characteristics of patients with HIV-associated CM were collected and collated. Predictors for relapse of HIV-associated CM were analyzed using univariate and multivariate logistic regression. Survival probability in cases of CM relapse was determined by Kaplan-Meier survival curves. Results During the study period, 87 of 348 (25.0%) HIV patients experienced relapse of CM. CD4+ T-cell counts, antiretroviral therapy (ART) status, and the time from symptom onset to presentation were all statistically associated with relapse of CM (p=0.013, 0.018 and 0.042, respectively). The overall survival among 46 HIV CM relapse patients whose survival information was traceable, was 78.3%. The proportion of patients who died after antifungal treatment for CM was greater in those whose interval from symptom onset to presentation was ≥ 4 weeks, compared with those whose interval from symptom onset to presentation was < 4 weeks (p=0.0331). Conclusions In order to reduce the rate of relapse of CM and increase the likelihood of survival of these patients, it is critically important to promote the importance of ART before CM overtly manifests, emphasize expeditious consultation when any CM-associated clinical symptoms occur, and individualize the timing of ART initiation according to indicators which may reflect the severity of CM.